Assessing strategies to improve resilience for the poor in fragile and low-income settings - CGIAR Research Program on Policies, Institutions, and Markets (2017)
Studies in Mali and Yemen assess the effectiveness of social protection programs in fragile and low-income settings, particularly conflict-affected areas, through opportunistic data collection in regions where conflict broke out while research was ongoing. New work in Ethiopia explicitly tests alternative strategies to reach the poor in a fragile setting.